A method to identify VR-based set-up to foster elderly in design evaluation. (2016) - Mengoni, Maura; Raponi, Damiano; Ceccacci, Silvia
User involvement during design process is an important issue in inclusive design (ID). To this purpose, in the last years, virtual reality (VR) technologies have been introduced to construct virtual prototypes, in order to allow test with users even at the end of the conceptual design phase. The present paper aims to propose a method to support the selection of VR interaction technologies, which can be suited by end users accordingly to their physical and cognitive abilities. The proposed method is applied in order to compare the main VR interaction technologies with the objective to identify an optimal low-cost VR set-up to involve elderly people in evaluation of an innovative concept of kitchen environment which implement smart grid and home automation technologies.